GLOBALIZATION AND GROSS DOMESTIC PRODUCT CONSTRUCTION IN ASEAN - Muhammad Sri Wahyudi Suliswanto; David Kaluge (Economic Journal of Emerging Markets, 2010)
There is no more doubt about the importance of economic growth, which can be calculated fromGross Domestic Product (GDP). This research analyzes the role of globalization on GDP inASEAN-5 by estimating panel data. It uses a fixed effect approach to accommodate various characteristicsin the countries. To accommodate such variation, it assumes that the intercepts variesacross these countries, while the slopes remain similar. Based on the estimation result, it suggeststhat net export and foreign direct investment represent the globalization process. Both have positiveand significant influences on GDP in the corresponding countries.Keywords: Globalization, international trade, foreign direct investment, gross domestic productJEL classification numbers: E01, F51, F43